2013
DOI: 10.1371/journal.pone.0056089
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 Attenuates Anoxia/Reoxygenation-Induced Cardiomyocyte Apoptosis by Inhibition of PKCβ/JNK Pathway

Abstract: BackgroundInterleukin-33 (IL-33) is a new member of the IL-1 cytokine family. The objectives of present study are to assess whether IL-33 can protect cardiomyocytes from anoxia/reoxygenation (A/R)-induced injury and the mechanism involved in the protection.MethodsCardiomyocytes derived from either wild type or JNK1−/− mice were challenged with an A/R with or without IL-33. Myocyte apoptosis was assessed by measuring caspase 3 activity, fragmented DNA and TUNEL staining. In addition, cardiomyocyte oxidative str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 31 publications
4
16
0
Order By: Relevance
“…Previous studies have shown that Nar has a strong cardioprotective effect because of its powerful antioxidant properties. In accordance with previous studies, [31][32][33] we found that A/R induced a variety of pathological changes in H9c2 cells. 30 However, the mechanism by which Nar protects against I/R-induced myocardial injury is still not well defined.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have shown that Nar has a strong cardioprotective effect because of its powerful antioxidant properties. In accordance with previous studies, [31][32][33] we found that A/R induced a variety of pathological changes in H9c2 cells. 30 However, the mechanism by which Nar protects against I/R-induced myocardial injury is still not well defined.…”
Section: Discussionsupporting
confidence: 93%
“…This demonstrates that myocyte TGFbetaR1-dependent signaling is not confined to the myocyte itself but that intercellular crosstalk originating from the myocyte can ultimately drive IL-33 expression in non-myocyte cells. Protection against ischemic injury by IL-33 has also been linked to JNK inhibition and reduced apoptosis 32, 48 , and we observed reduced JNK phosphorylation in TGFbetaR1 cKD animals.…”
Section: Discussionsupporting
confidence: 60%
“…It is a ligand for the ST2 receptor and protective against several forms of heart disease 3032 . In infarcted control hearts, Il33 gene expression rose slightly more than 2-fold, but increased nearly 10-fold in TGFbetaR1 cKD (Figure 7A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reperfusion injury is initiated by decreased endothelialderived nitric oxide (NO) which occurs within 5 min of reperfusion [2], and may in part be explained by PKC II mediated activation of NADPH oxidase, which occurs upon cytokine release during MI/R [3]. PKC II activity is increased in animal models of MI/R and known to exacerbate tissue injury [4,5]. PKC II is known to increase NADPH oxidase activity in leukocytes, endothelial cells and cardiac myocytes via phox47 phosphorylation, and decrease endothelial NO synthase (eNOS) activity via phosphorylation of Thr 495 [6][7][8].…”
Section: Introductionmentioning
confidence: 99%